Genotyping of Toxoplasma gondii and Sarcocystis spp. in road-killed wild mammals from the Central Western Region of the State of Sao Paulo, Brazil - Richini-Pereira, Virginia Bodelao; Marson, Pamela Merlo [UNESP]; Silva, Rodrigo Costa da; Langoni, Helio [UNESP] (Soc Brasileira Medicina Tropical, 2016)
Introduction: Road-killed wild animals host zoonotic pathogens such as Toxoplasma gondii, offering a new opportunity for the epidemiological study of these infectious organisms. Methods: This investigation aimed to determine the presence of T. gondii and other apicomplexan parasites in tissue samples of 64 road-killed wild animals, using polymerase chain reaction (PCR). Positive samples were then typed by PCR-restriction fragment length polymorphism (RFLP) using 7 markers: SAG1, 5'-3' SAG2, SAG3, BTUB, c29-6, PK1, and Apico. PCR-RFLP targeting 18S ribosomal RNA (rRNA) genes was also performed on all samples to detect other apicomplexan parasites. Results: T. gondii DNA was detected in 16 tissue samples from 8 individual animals, as follows: 1 Cerdocyon thous (crab-eating fox), 1 Didelphis albiventris (white-eared opossum), 1 Lutreolina crassicaudata (lutrine opossum), 2 Myrmecophaga tridactyla (giant anteater), 1 Procyon cancrivorus (crab-eating raccoon), and 2 Sphiggurus spinosus (Paraguay hairy dwarf porcupine). Seven different T. gondii genotypes were identified, 6 of which were novel. Typing by 18S rRNA verified these 16 T. gondii-infected samples, and identified 1 Sarcocystis spp.-infected animal [Dasypus novemcinctus (nine-banded armadillo)]. The amplified T. gondii (GenBank accession No. L37415.1) and Sarcocystis spp. 18S rRNA products were confirmed by sequencing. Conclusions: Our results indicate that T. gondii is commonly present in wild mammals, which act as sources of infection for humans and animals, including other wild species. The approach employed herein proved useful for detecting T. gondii and Sarcocystis spp. in the environment and identifying their natural reservoirs, contributing to our understanding of host-parasite interactions.
Keywords: Road-killed animal; Toxoplasma gondii; Sarcocystis spp; Genotyping; Molecular techniques